SARS-CoV-2 M Protein Facilitates Malignant Transformation of Breast Cancer Cells - Nguyen, Hoai-Nga Thi; Kawahara, Marie; Vuong, Cat-Khanh; Fukushige, Mizuho; Yamashita, Toshiharu; Ohneda, Osamu (Frontiers in Oncology, 2022)
Coronavirus disease 2019 (COVID-19) has spread faster due to the emergence of SARS-CoV2 variants, which carry an increased risk of infecting patients with comorbidities, such as breast cancer. However, there are still few reports on the effects of SARS-CoV2 infection on the progression of breast cancer, as well as the factors and mechanisms involved. In the present study, we investigated the impact of SARS-CoV-2 proteins on breast cancer cells (BCC). The results suggested that SARS-CoV-2 M protein induced the mobility, proliferation, stemness and in vivo metastasis of a triple-negative breast cancer (TNBC) cell line, MDA-MB-231, which are involved in the upregulation of NF-κB and STAT3 pathways. In addition, compared to MDA-MB-231 cells, the hormone-dependent breast cancer cell line MCF-7 showed a less response to M protein, with the protein showing no effects of promoting proliferation, stemness, and in vivo metastasis. Of note, coculture with M protein-treated MDA-MB-231 cells significantly induced the migration, proliferation, and stemness of MCF-7 cells, which are involved in the upregulation of genes related to EMT and inflammatory cytokines. Therefore, SARS-CoV2 infection might promote the ability of aggressive BCC to induce the malignant phenotypes of the other non-aggressive BCC. Taken together, these findings suggested an increased risk of poor outcomes in TNBC patients with a history of SARS-CoV2 infection, which required a long-term follow-up. In addition, the inhibition of NF-κB and STAT3 signaling pathways is considered as a promising candidate for the treatment of worsen clinical outcomes in TNBC patients with COVID-19.